Facility Service Environments, Staffing, and Psychosocial Care in Nursing Homes - Zhang, Ning Jackie (CENTERS for MEDICARE & MEDICAID SERVICES, 2008)
Using 2003 Online Survey Certification and Reporting (OSCAR) data for Medicare and Medicaid certified facilities (N=14, 184) and multinomial logistic regression this study investigated if (1) psychosocial care quality was better in facilities where State requirements for qualified social services staffing exceeded Federal minimum regulations and (2) facility service environments are associated with psychosocial care quality. For-profit status and higher percentage of Medicaid residents are associated with lower quality. Staffing, market demand, and market competition are associated with better quality. Psychosocial care quality is more associated with payer status and market forces and less with regulatory requirements.